KAJIAN EVALUASI EKONOMI PEMANFAATAN RUANG TERBUKA PESISIR TELUK PALU - Irwan, Andi (Katalogis, 2016)
Palu Bay as an important role in the growth area of the city and affect the chain of elements of economic growth so as to have a very strong appeal and the number of dense population and very diverse. Palu Bay Area region is a strategic region in the context of the development of Central Sulawesi province, especially the town of Palu, the economic sectors that supported the trade, hotel and restaurant sector that contributed the most to the economy of the city. This study aims to conduct a study on the economic evaluation of the use of public open space Palu Bay to find out; economic income of small businesses in the utilization of Palu bay open spaces,Â  factors that affect the utilization of public spaces and improving the local economy; and to investigate the potential and contribution to the economic communities on the use of Palu bayÂ  public space. This research is descriptive qualitative rationalistic paradigm. Qualitative approaches in research that by outlining the potential for community efforts on public space bridge coast of Besusu Barat, population / labor and quantify the contribution of space utilization for increasing people's income which is the object of research. The results showed that (1) children's games rental business as the largest contributor to economic income communities that reaches Rp1.117.580.000 / month, (2) Of the trades, types of eateries a contributor to economic potential reach Rp30.500.000 per month, then the souvenir sales and other businesses with revenues of Rp27.450.000 per month, as well as business mix and beverage kiosk with monthly income of Rp14.450.000. (3) For services business / profession is a kind of business people who are not significantly contributed to the regional economy accounted for only the opinion of Rp11.500.000 per month, comprising of photographers at Rp4.500.000, businesses sbesar Rp2.000.000 security, and business services parking Rp5,000,000 per month.